The Influence of Democratic Leadership Style, Team Work and Work Discipline on Employee Morale: Pengaruh Gaya Kepemimpinan Demokratis, Team Work dan Disiplin Kerja Terhadap Semangat Kerja Karyawan - Nurjannah, Novia Siti; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine the effect of Democratic Leadership Style, Team Work and Work Discipline on the morale of the employees of the Surabaya Main Branch Post Office. The approach used. In this research is a quantitative approach. The population in this study was 130 employees. Sampling techniques using random sampling techniques. Samples in this study were 100 respondents. Analysis Using SPSS Software.The results of this study indicate that partially and simultaneously Democratic Leadership Style, Team Work and Work Discipline compensation, work discipline and motivation affect the morale of the employees of the Surabaya Main Branch Post Office.